2017
DOI: 10.5935/0946-5448.20170011
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgo biloba in the treatment of tinnitus: An updated literature review

Abstract: Introduction: Tinnitus is one of the common diseases of the ear that is associated with numerous physical and mental disorders. One of the known mechanisms in the tinnitus area with unknown reason is oxidative events. Based on the prevalence and economic costs and physical-psychological side effects caused by tinnitus and the importance of finding a suitable solution for its prevention and treatment, the need for further studies becomes more obvious in this context. This review article aimed to review studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 38 publications
(41 reference statements)
0
23
0
1
Order By: Relevance
“…Garlic's effect on tinnitus is attributable to improve blood flow of cochlea as a result of its antiplaque formation ability and stabilizing blood pressure. 16,17…”
Section: Misoprostolmentioning
confidence: 99%
“…Garlic's effect on tinnitus is attributable to improve blood flow of cochlea as a result of its antiplaque formation ability and stabilizing blood pressure. 16,17…”
Section: Misoprostolmentioning
confidence: 99%
“…Looking through studies on Ginkgo biloba, we found contrary treatment effects on tinnitus, and a Cochrane review concluded that there was limited evidence to support the effectiveness for patients whose primary complaint was tinnitus [ 160 ]. This might be due to a lack of standard usage, a lack of optimal doses, and a lack of standard methodological measurements of efficacy [ 149 , 161 164 ]. The efficacy of tinnitus is likely to be the mixture of multiple ingredients, which might not be conducive to guiding the treatment and avoiding adverse effects.…”
Section: Tinnitus Management and Medicationsmentioning
confidence: 99%
“…Ginkgo biloba contains monoamine oxygenase inhibitors including ginkgolide and bilobalide as well as myricetin and quercetin flavonoids. Ginkgo biloba has antioxidant and protective effects on nerve cells in the brain, auditory cortex, and subcortical field because of which it can be used for the treatment of tinnitus [19] . Magnesium has been shown to minimise noise-induced vasoconstriction, caused by the formation of free radicals.…”
Section: Introductionmentioning
confidence: 99%